Multifeed EBG Dual-Band Antenna for Spatial Mission - A. Kanso; R. Chantalat; U. Naeem; H. Chreim; M. Thevenot; S. Bila; T. Monediere (International Journal of Antennas and Propagation)
We present the design of a multibeam reflector antenna fed by a multifeed dual-band electromagnetic band gap (EBG) antenna to achieve a high-gain multispot coverage for space applications. First, we design a dual-band EBG antenna in monofeed configuration. This antenna is composed of double-layer frequency selective surfaces (FSSs) arranged in the longitudinal direction and a square horn as a feed. Then, the same antenna in multifeed configuration is studied, and the results are compared to those obtained in monofeed configuration in order to emphasize the problem of coupling, generally encountered in multifeed configuration. Consequently, filters are used in order to reduce the parasitic interferences and obtain good radiation characteristics. As shown in this paper, the same EBG phase center is obtained in both frequency bands. Finally, we have studied the whole system composed of the offset reflector and the multifeed EBG dual-band antenna. An edge of coverage (EOC) gain higher than 42 dBi and sidelobes levels lower than −18 dBi are obtained over all spots.